ICA Zipa: variedad de papa para procesamiento. - Pineda Colorado, Ramón; Rodríguez B., Armando; Hernández C., Edgar; Estrada, Nelson (Universidad Nacional de Colombia - UNAL, 1995)
Papa-Solanum tuberosum